Sponsored links: Algebra eBooks
 

Help Index

A

B

C

D

E

F

G

H

I

J

K

L

M

N

O

P

Q

R

S

T

U

V

W

X

Y

Z

The Maxima on-line user's manual

Algebra Calculator

Search:

Desolve Calculator

Desolve

Function: desolve (<eqn>, <x>)

globalsolve:true;
Vs:120;
R:4;
L:4;
C:1;
de1: -Vs+R*C*diff(vc(t),t,1)+L*C*diff(vc(t),t,2)+vc(t)=0;
atvalue(vc(t),t=0,0);
atvalue(diff(vc(t),t),t=0,0);
sol:desolve(de1,vc(t));
plot2d(rhs(sol),[t,0,20]);
plot2d(C*diff(-60.0*t*%e^(-0.5*t)-120.0*%e^(-0.5*t)+120,t),[t,0,20]);
plot2d(C*diff(-60.0*t*%e^(-0.5*t)-120.0*%e^(-0.5*t)+120,t),[t,1,3]);
ilt(log((s^2+4*s+13)/(s^2)),s,t);

Function: desolve ([<eqn_1>, ..., <eqn_n>], [<x_1>, ..., <x_n>]) The function desolve solves systems of linear ordinary differential equations using Laplace transform. Here the <eqn>s are differential equations in the dependent variables <x_1>, ..., <x_n>. The functional dependence of <x_1>, ..., <x_n> on an independent variable, for instance <x>, must be explicitly indicated in the variables and its derivatives. For example, this would not be the correct way to define two equations:

eqn_1: diff(f,x,2) = sin(x) + diff(g,x); eqn_2: diff(f,x) + x^2 - f = 2*diff(g,x,2);

The correct way would be:

eqn_1: diff(f(x),x,2) = sin(x) + diff(g(x),x); eqn_2: diff(f(x),x) + x^2 - f(x) = 2*diff(g(x),x,2);

The call to the function desolve would then be desolve([eqn_1, eqn_2], [f(x),g(x)]);

If initial conditions at x=0 are known, they can be supplied before calling desolve by using atvalue.

          (%i1) diff(f(x),x)=diff(g(x),x)+sin(x);
                           d           d
          (%o1)            -- (f(x)) = -- (g(x)) + sin(x)
                           dx          dx
          (%i2) diff(g(x),x,2)=diff(f(x),x)-cos(x);
                            2
                           d            d
          (%o2)            --- (g(x)) = -- (f(x)) - cos(x)
                             2          dx
                           dx
          (%i3) atvalue(diff(g(x),x),x=0,a);
          (%o3)                           a
          (%i4) atvalue(f(x),x=0,1);
          (%o4)                           1
          (%i5) desolve([%o1,%o2],[f(x),g(x)]);
                            x
          (%o5) [f(x) = a %e  - a + 1, g(x) =

x cos(x) + a %e - a + g(0) - 1]

          (%i6) [%o1,%o2],%o5,diff;
                       x       x      x                x
          (%o6)   [a %e  = a %e , a %e  - cos(x) = a %e  - cos(x)]

If desolve cannot obtain a solution, it returns false.

(%o1)                                true
(%i2) 

Desolve Example

Related Examples

desolve-diff

eqn_1:'diff(x,t)=1*x(...

eqn_2:'diff(y,t)=-9*x...

desolve([eqn_1,eqn_2]...

Calculate

desolve-diff

desolve([diff(f(x),x)...

Calculate

desolve-diff

eq:'diff(y(x),x,2)=y(...

desolve(eq,y(x));

Calculate

desolve-diff

eq:'diff(y(x),x)=y(x)...

desolve(eq,y(x));

Calculate

desolve-diff

desolve(['diff(y(x),x...

Calculate

desolve-diff-sin

desolve(diff(y(x),x,2...

Calculate

desolve-diff-eliminate-subst

eq1 : diff(y0(t),t) =...

eq2 : diff(y1(t),t) =...

eq3 : diff(y2(t),t) =...

Calculate

desolve-diff

eq1:diff(y(x),x,1)+P*...

desolve(eq1,y(x));

Calculate

desolve-diff-ev

ed1:'diff(x(t),t)=x(t...

ed2:'diff(y(t),t)=y(t...

[x(t),y(t)]=desolve([...

Calculate

desolve-diff-eliminate-subst

eq1 : diff(y0(t),t) =...

eq2 : diff(y1(t),t) =...

eq3 : diff(y2(t),t) =...

Calculate